PERADILAN BERBASIS HARMONI : WAWASAN BARU DALAM PENYELESAIAN KASUS KRIMINAL - Karolus Kopong Medan (Masalah-Masalah Hukum, 2012)
This study tried to offer a new theoretic perspective about settlement form of criminal case. The offer based on Lamaholot society in East Flores – East Nusa Tenggara experience which always gives a harmony value as a priority combine with Adat tradition of peace mela sare or tapan holo into every settlement practice of criminal case. What Lamaholot society was constructed and other societies in Indonesia did, actually emphasis that the final goal of every judicial process is not only to judge which one is wrong and which one is right, either not only to find the truth and justice. But, additionally judicial process has to make a harmony or rebuild a social relation among the victims of conflict. Even, a social harmony that was built is managed generally as individual, and collective context, and as also vertically to the Almighty God. The judicial orientation with rich philosophy of harmony as figure out in the peace of the Adat tradition mentioned before can be applied to social sphere, because actually the harmony value is everybody's dream in the world.Keywords : judicial, criminal, harmony, adat tradition, Lamaholot society.